Potential biofuel feedstocks and production in Zambia - Paul C. Samboko; Mitelo Subakanya; Cliff Dlamini (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
The need for energy security and climate change mitigation have increased blending mandates worldwide; in Southern Africa, demand for biofuels could increase following South Africa's planned blending mandates. However, land constraints limit local industry expansion, with demand likely to be met in land-abundant countries. This paper reviews the status of the biofuels industry in Zambia, as a land-abundant country, for the local and wider Southern African market. It identifies potential biofuel feedstocks as crucial elements for establishing a viable industry. Identified potential bioethanol feedstocks include sugarcane, cassava, sweet sorghum, and maize; for biodiesel, soya beans, sunflower, and groundnuts are the likely feedstocks of choice. However, current production levels are inadequate to meet growing regional biofuels demand, but there is scope for expansion if productivity and production can be increased. Presently, there is no commercial biofuel production, but a fairly adequate policy, regulatory, legal, and institutional framework exists.
Keywords: Q16; Q18; Q12; O13; 330; biofuels; feedstocks; Zambia; Southern Africa